Kinetics of the Inhibition of Plasmin in Acidified Human Plasma - Lijnen, H R; Maes, M; Castel, M; Samama, M; Collen, D (Thrombosis and Haemostasis, 1982)
Acid-treated human plasma is a competitive inhibitor of the hydrolysis of D-Val-Leu-Lys-Nan (S-2251) by plasmin. The rate of hydrolysis is decreased to 50% by 750 fold diluted acidified normal plasma and by 60 fold diluted acidified α2-antiplasmin depleted plasma (α2-antiplasmin concentration less than 2%). These findings suggest that α2-antiplasmin is a contributary but not the main competitive inhibitor of acidified plasma. This interpretation is supported by the finding that α2-antiplasmin depleted plasma reconstituted with purified α2-antiplasmin inhibits the hydrolysis of S-2251 by plasmin at a 125 fold dilution following acidification and by the finding that in a purified system acid inactivated α2-antiplasmin inhibits the hydrolysis of S-2251 by plasmin with a Ki of 25 nM. Thus, besides α2-antiplasmin, other plasma proteins which are at least in part eliminated by the removal of α2-antiplasmin from plasma by immunoadsorption appear to be competitive inhibitors for plasmin in acidified plasma. It is suggested that several competitive inhibitors for plasmin are present and/or generated in acidified plasma and that these inhibitors may at least in part be responsible for the variability in the results of measurements of plasminogen and/or plasmin in plasma following acidification.
Keywords: Acidified human plasma; Inhibition of plasmin; α2-Anti-plasmin; Plasmin inhibitors in plasma